Pengaruh Pemanfaatan Internet terhadap Kegiatan Belajar Siswa SMA di Wonogiri - Sri Tomo; Doddy Satriya Perbawa (Politeknosains, 2017)
Demands that must be done High School in the implementation of the learning process that utilizes information and communication technology to face various obstacles that are not simple. The main problem that is often faced by the School is the lack of facilities infrastructure, human resources and learning resources. While the teacher is a skill pengampu knowledge of additional teaching materials, and teacher motivation in the use of the Internet as a supporter of learning. This study aims to determine the utilization of the internet by high school students as a supporter of learning and its influence on the motivation of high school students in the city of Wonogiri. In carrying out this research activity used method: dispersion questionnaire for data retrieval, validity test, reliability test, normality test subsequently tested hypothesis by linear regression. From the research results obtained that the use of internet and motivation to learn a positive effect on student learning activities.